علامات الوقف وأثرها في إبراز إعجاز القرآن الكريم دراسة تحليلية في سورتي الكهف ومريم - Mohammad Hikmat Shaker (Universiti Sains Islam Malaysia, 2024)
The research aiming at explaining the terms of the scientists of Holy Quran sciences and the reasons behind the differences in stopping and starting marks for each one of Al anbari, Abu Jafer Alnahas, and Aldani, and their applications on the Holy Quran through two Surah Alkahef and Mariam and this subject is really important for relationship with the Holy Quran. After the reading and research I found that stopping and starting marks has the high influence in explaining the rhetorical meaning and the aesthetic for the Holy Quran. In addition to the interpretative side in depth for each Ayah and what is the exact meaning, I found in the same time that there are different reasons behind the scientists differences in stopping and starting terms also there are opposite opinion between them relate to stopping marks in the same Ayah. Some of them say that this position complete stop or good stop which makes the learner hesitate which one is more near to correction. These differences due to scientists of Quran explanation for the need of the World in this type of knowledge especially in this Art which is different to other important sciences and support to know where we stop in the Ayah. The writer of this thesis follow in his methodology the library study which aiming at gathering information and analyze it and establish the results and connect with each other to implement the purposes along with examples, I conclude from this study with important results, especially to know the reasons which lead to the differences between proper scientists of the Holy Quran in regard to stopping terms in one Ayah and some of them refer to grammar, Tafseer, Quran drawing, Alhadeith acceptance and rejection, counting the Ayahs, rhetorical science, context, perfect miracles, and Al-Qraat (different reading of Quran),Although, there are differences in schools and the scientist way of performance but all people agree on the importance of this science, because it an important side in reading Quran which is clear in places where the reader should stand with what agree with perfect Tafseer and the meaning integrity according to what Allah expect of people to understand the Quran meaning.